Mistifikasi Prabowo-Sandi dalam Iklan Politik - Safarudin Safarudin (PERSPEKTIF, 2021)
This study aims to determine the mystification of political messages displayed in the campaign materials for the Prabowo-Sandi candidate pair in the 2019 presidential election, namely the denotative and connotative meanings contained in the advertisement. The campaign material to be examined is the official Prabowo-Sandi advertising video which was submitted to the General Election Commission. This study uses semiotic analysis to examine the sign system in the video advertising campaign for the Prabowo – Sandi candidate in the 2019 General Election as part of the commodification of content through the practice of mystification. This research finds several forms of mystification: Prabowo-Sandi is imaged as a fair leader who will bring prosperity and a figure who adheres to pluralism, respects differences, and upholds diversity. Conditions that are very opposite to the objective circumstances of the candidate and the values held by the bearers and supporters. The conclusion of this study is that political advertising is deeper (connotative) to mystify the figure of Prabowo-Sandi as a national patriot who will lift society from national problems. Not only political leaders, Prabowo-Sandi is also imaged as a cultural leader through the symbolization of the Javanese king (keris and garuda-motif batik) who respects other cultural diversity. The emergence of traditional symbols of Lombok, Minangkabau, and Bali is an attempt to mystify Prabowo-Sandi as a figure who has concern for the cultural diversity of the archipelago. Apart from culture, Prabowo-Sandi's mystification can be seen through the symbolization of religious diversity.